Evaluation of Use of Social Media in Marketing Communication Activities of Institutions - Ünal Çimçek, Selin (European Scientific Journal, ESJ, 2018)
Rapidly evolving technology has led to the differentiation of communication tools used by institutions and brands in marketing communication activities. Social media with low-cost, fast feedback providing a possibility to access large masses in a shorter time with Web 2.0 technology has become a preferred tool for brands. In this study the concepts of social networks and social media is explained within the scope of communication studies, in relation with public relations, advertisement, and sales promotion. In the scope of the research; it has been benefited from the statistical information inferred from the data based on Facebook, Twitter, and Instagram during 1-31 January 2018 period by SocialBrands, which measures more than 25 thousand brands’ social media performances. Social media marketing communications studies of two of the successful brands in home decoration sector in Turkey, Madam Coco and English Home, have been analyzed by the data of SocialBrands. It has been tried to explain that brands become more successful in brand communications with social media through which they find the measurable and fast opportunity to determine their target audience.